Investigação teórica da cinética de formação de hidratos de metano e dióxido de carbono - Zanon, Gabriel Nogueira (2017)
Hydrates are crystal structures that can be formed from the interaction of water molecules and low molecular weight gases such as methane, ethane, propane and carbon dioxide. These structures are formed under favorable thermodynamic conditions. They are high pressure and low temperature. During the oil and gas production processes, one of the most challenges faced is the flow assurance, consisting of a set of activities in order to avoid a presence of factors that can reduce or prevent the continuous flow. The hydrates formation in the oil and gas lines represents an objection to the flow assurance, resulting in productive losses and equipment damage, since they are solid particles. The kinetics of hydrate formation describes the phenomena related to time in the process of hydrate formation. Currently the number of studies dedicated to the hydrate formation kinetics is relatively limited, especially when confronted with research on equilibrium thermodynamics. In this context this work seeks to collaborate for a better understanding of the hydrate formation kinetics. Therefore, in a first moment it will be presented a theoretical foundation related to the hydrate and its formation kinetics, as well as some mathematical models to improve the formation kinetics mechanism. Afterwards Skovborg and Rasmussen (1993) model will be used in the hydrate kinetic modeling of methane and carbon dioxide. For the validation will be used experimental data available in the literature.